Bandas de música e igreja católica no Rio Grande do Norte: estratégias e táticas em espaços religiosos potiguares - Sobrinho Filho, Antonio Tenório (2021)
The political and legal origin of the Captaincy of Rio Grande dates back to the 16th century. After a few centuries since the first colonizing expeditions carried out under the aegis of the Portuguese Crown, also passing through the Iberian Union and the Dutch domain, Natal has become one of the oldest cities in Brazil, having been chosen as the official date of its foundation, 25 December 1599. The Roman Apostolic Catholic Church started operating in the territory of the state of Rio Grande do Norte in the 16th century, whether through religious linked to regular or secular clergy. Music, in turn, was also part of the process of colonizing the body and mind of the native peoples of this part of our country, its effects have been expanded to the present day, not being restricted only to the Indians of yore. Inevitably, music and the Catholic Church walked and still walk together in the contemporary world, as well as most of the existing religions in the history of mankind. The scarcity of musicological research aimed at Wind Bands in Rio Grande do Norte was the main motivating factor in this work. That said, the objective of this research is to know and understand the existing relationships between religious of the Catholic Church and the musicians of the Philharmonic Bands in and from Rio Grande do Norte. The time frame ranged from the date of publication of the Motu Proprio Tra Le Sollecitudini (1903) to the officialization of the Apostolic Constitution Sacrosanctum Concilium (1963), resulting from the Second Vatican Council. With regard to the observed space, the current territory of Rio Grande do Norte was focused, taking into account the respective limitations of the research. In order to achieve the objectives of this research, ecclesiastical legislation on sacred music was used, information contained in period newspapers of the period analyzed (available in the Brazilian Digital Library of the National Library), in addition to musical sources collected from collections of different Music Bands from Rio Grande do Norte. In order to support our reflections, we opted for the use of the concepts of "strategy" and "tactics"; as well as the notions of “space” and “place”, developed by the philosopher Michel de Certeau (1998). Reviewing the academic production on Music Bands in Rio Grande do Norte, it was noticed that a large part of these works is linked to the field of Musical Education and / or Performance, thus denouncing, in this way, the almost inexistence of musicological works on the musical past that specific audience. The results achieved through this research will make it possible to take a new look at this part of the Brazilian territory, further reinforcing the need for new musicological research with a focus on Wind Bands, as well as paying attention to the existence of multiple cultural agents who have acted in this region, be they whether they are religious or not. Another point to be highlighted concerns the musical collections of the artistic institutions studied. The application of the concepts of "Strategy" and "Tactics" on the performance of instrumentalist musicians in religious-Catholic environments made it possible to know the types of relations existing between the Church from Rome and its representatives in the territory from Rio Grande do Norte, as well as helping to understand the existing relationship between the musicians of the Philharmonics and the religious in the heart of regional Catholicism. It also denounced the existence of divergences, different forms of interpretation of Catholic legislation, forms of normative adaptations and even non-compliance with ecclesiastical norms. In short, it was possible to identify the use of strategies and tactics exercised by both the religious of the Catholic Church and the musicians of the Philharmonics potiguares.